Efficiency of net primary biomass production of Eucalyptus dunnii Maiden seedlings. - Costa Junior, Sérgio; Dalla Corte, Ana Paula; Behling, Alexandre; Trautenmuller, Jonathan William; Woycikievicz, Antonio Pedro Fragoso; Borella, Juliane (Floresta, 2020)
The objective of this study was to assess the influence of planting density, growth environment and the seasons over the conversion efficiency (εb) of intercepted photosynthetically active radiation into biomass of Eucalyptus dunnii Maiden seedlings. An experiment was carried out using two plantings densities (100 % and 50 % occupancy), two growth environments (natural environment and greenhouse environment) during two growth seasons (summer and fall). Determinations of net primary biomass production, leaf area index and interception of the photosynthetically active radiation were taken, which allowed the calculation of εb. Null hypothesis was rejected - the factors investigated (plant density, growth environment and seasons) influenced the values of εb. The higher observed εb was 7.59 g MJ‑1, obtained in the experiment conducted during summer, under greenhouse conditions and at 100 % tray density. Factors did not depend on εb, pointing that the greater εb was observed in the greenhouse environment and with a planting density of 100 %, independently of the season. Therefore, the factors assessed had influence over net primary biomass production of Eucalyptus dunnii Maiden seedlings, resulting in a longer or shorter residence time of the seedlings in the nursery.